2022
DOI: 10.3390/ijerph19073835
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping Styles and Depressive Symptoms in Geriatric Patients: Understanding the Relationship through Experiences of Integrity and Despair

Abstract: Older persons are often confronted with challenging events in their lives. Religion can offer them a way to deal with these challenges. The study of religious coping styles helps us to understand how people find support in their religion or wrestle with aspects of their religion when they are confronted with difficulties. Especially when older adults face illness and hospitalization, religious coping styles might be triggered. Despite the fact that the public role of religion, especially Christianity, is dimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
0
5
0
1
Order By: Relevance
“…Second, consistent with extant studies (see the literature review section), this study found that there are some religious coping strategies that Tibetan people may use to sustain mental health in the face of a disaster. Although the physio‐psychological mechanism has not been completely revealed (Buelens et al, 2022; Desmet et al, 2022), it has been argued that positive religious coping may serve an adaptive function that yields positive outcomes such as hope, life satisfaction, and purpose (Ano and Vasconcelles, 2005; Buelens et al, 2022). Post‐disaster psychological interventions should consider the potential value of traditional religious coping strategies, especially when ‘modern science‐based’ psychological intervention strategies have limited effects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, consistent with extant studies (see the literature review section), this study found that there are some religious coping strategies that Tibetan people may use to sustain mental health in the face of a disaster. Although the physio‐psychological mechanism has not been completely revealed (Buelens et al, 2022; Desmet et al, 2022), it has been argued that positive religious coping may serve an adaptive function that yields positive outcomes such as hope, life satisfaction, and purpose (Ano and Vasconcelles, 2005; Buelens et al, 2022). Post‐disaster psychological interventions should consider the potential value of traditional religious coping strategies, especially when ‘modern science‐based’ psychological intervention strategies have limited effects.…”
Section: Discussionmentioning
confidence: 99%
“…Most religions emphasize living purposefully, involving submission to a divine entity and offering rituals that provide comfort and influence to patients and their families during their final days. As the pandemic unfolds, participants acknowledge the role of family and religious leaders in fostering spiritual renewal and meaning [33] within the provision of quality EoLC.…”
Section: Instilling Faith To Embrace Fatementioning
confidence: 99%
“…In addition to the stress and fear of contracting the virus [27], nurses' accounts from previous lived experience studies describe their unrelenting efforts to provide comfort and care to their patients [28][29][30]. Furthermore, nurses too are required to use a variety of coping mechanisms to cope with difficult times [31,32], whether they are religious oriented [33] or counselling among peers [34,35]. More importantly, amidst all of these factors, nurses are expected to be resilient as the work paradigm changes [36,37], while maintaining close communication with family members of the patients [38].…”
Section: Introductionmentioning
confidence: 99%
“…People may have distressing emotions when they encounter conditions in their lives that they perceive to be unpleasant. People employ coping techniques to deal with these circumstances and feelings (Desmet et al, 2022). Additionally, religion might be crucial in managing.…”
Section: Introductionmentioning
confidence: 99%